The Role of Accounting Information in the Company's Decision-Making Process - Ikram, Krit; Ahmed, Aftiss (International Journal of Psychosocial Rehabilitation, 2020)
An accounting system is represented as the language of business because cost, price, sales volume, profits, and return on investment are all accounting measurements, and the purpose of accounting is to provide information that is useful for decision-making. This paper aimed to explain and clarify the importance of using accounting information in the decision-making process to meet the requested administrative needs to rationalize the administrative decision of the company. In the field of data, we used primary sources and secondary sources to achieve the objectives of the study and answer its questions. Through this approach, we obtained the data constituting the theoretical framework of the study. While the practical setting depends on an interview.